Improvisation, Blankness and Mesmerism: Mike Leggett and Ian Breakwell’s Sheet and the Two Avant-Gardes - Kieran Devaney (Angles)
This article examines Mike Leggett and Ian Breakwell’s short film Sheet. Though little scholarship exists on Sheet, the enigmatic quality of the film and the sheet that gives it its name has given rise to a number of contrasting interpretations. The article discusses two opposing accounts of the film, one which sees it as being a film haunted by the ghostly presence of the titular sheet, and which contains some form of narrative and resolution, and one which sees it as an example of structural film, characterised by repetition and formal concerns. I align these two interpretations with Peter Wollen’s article on the two avant-gardes in contemporary film and argue that Leggett and Breakwell’s work, through their improvisatory approach, triangulates Wollen’s distinction, and allows both interpretations to be simultaneously true. In addition, I discuss the way in which the film re-examines a theme found in filmmaking in the immediate post May ’68 moment, of characters moving from the urban to the rural. As such, the film can be seen as expressing the anxieties and concerns of that period, both political and artistic.